Correlation between Shallow Benthic Zones and calcareous plankton Zones at the Bartonian-Priabonian transition: preliminary results from the Varignano section (Trento Province, northern Italy). - PAPAZZONI, Cesare Andrea; Moretti A.; Luciani V.; Fornaciari E.; Giusberti L. (Faculdad de Ciencias e Tecnologia Universidade Nova de Lisboa, 2013)
The Varignano section (Trento province, northern Italy), deposited in bathyal paleoenvironment, contains eight resedimented bioclastic levels with larger foraminifera, thus providing the exceptional chance to directly correlate the Shallow Benthic Zones (SBZ) with the calcareous plankton standard Zones around the Bartonian-Priabonian transition. Moreover, this section is only 80 km far from the Alano di Piave section (Veneto region), candidate to host the GSSP of the base of Priabonian, where this direct correlation is hampered by the absence of resedimented levels across the critical interval. The preliminary results of the integrated calcareous plankton and larger foraminifera study evidence that the extinction of morozovellids and large acarininids (E13-E14 boundary) occurs within SBZ 18 and not at the boundary SBZ 18-19 as usually considered.